Private Property and its Elastic Nature - Rivera Sabatés, Vidal (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2014)
Possession, real property right par excellence, is the greatest dominating power that the legal system allows us to take on a certain good. Analysis of the legal definition captured in article 348 of the Civil Code and reviews comments, as much technical as social/ political, which the latter has arisen. Meaning and scope of one of the main features of possession: its elasticity or spreading power.